2013
DOI: 10.1292/jvms.12-0141
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Differences in Peripheral Blood and Gene Profiling in the Liver and Lymphocytes in Japanese Black Cattle with Growth Retardation

Abstract: ABSTRACT. Japanese Black cattle occasionally demonstrate growth retardation despite sufficient nutrient intake. To clarify hormonal and transcriptional characteristics, we investigated differences in blood components, including hormones, and differences in exhaustive gene expressions in the liver and peripheral lymphocytes of six cattle with growth retardation (GR cattle) and eight control cattle of the same age and pedigree with normal growth. Hematocrit values and concentrations of hemoglobin, serum albumin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The high rate of marbling in the Japanese breeds is related to certain blood metabolites [33][34][35][36][37][38]. Plasma TC may be higher in the Wagyu animals, compared with Holstein steers [65], and our TC and TG findings are consistent with this idea.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The high rate of marbling in the Japanese breeds is related to certain blood metabolites [33][34][35][36][37][38]. Plasma TC may be higher in the Wagyu animals, compared with Holstein steers [65], and our TC and TG findings are consistent with this idea.…”
Section: Discussionsupporting
confidence: 84%
“…Monitoring some of these parameters can help in assessing how efficiently the animals use the supplied nutrients [32]. In Wagyu cattle, the main metabolic parameters related to marbling and growth rates are cholesterol, glucose, and urea [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…How we can identify indicators of slight changes in their conditions? Monitoring of the liver is an effective measure for assessing animal body conditions and the values of various physiologically relevant molecules in the peripheral circulatory system in response to body conditions are usually measured by biochemical and physiological methods (Ishida et al, ; Keogh, Kenny, Cormican, Kelly, & Waters, ; Shi et al, ). Recently we reported that the expression profiles of some genes in PBLs reflect changes in body calcium (Sasaki et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, GAPDH showed a very stable state. Other researchers also used GAPDH as an internal control in goats ( He et al, 2012 ; Sun et al, 2013 ; Sun et al, 2017 ), cattle ( Ishida et al, 2013 ; Wang et al, 2017 ), yak ( Pan et al, 2015 ; Qin et al, 2015 ), sheep ( Sun et al, 2019 ; Liu et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%